Comparisons of Traditional Metabolic Markers and Compensatory Reserve as Early Predictors of Tolerance to Central Hypovolemia in Humans. Issue 1 (July 2018) - Schiller, Alicia M.; Howard, Jeffrey T.; Lye, Kristen R.; Magby, Christian G.; Convertino, Victor A.
Abstract : ABSTRACT: Circulatory shock remains a leading cause of death in both military and civilian trauma. Early, accurate and reliable prediction of decompensation is necessary for the most efficient interventions and clinical outcomes. Individual tolerance to reduced central blood volume can serve as a model to assess the sensitivity and specificity of vital sign measurements. The compensatory reserve (CRM) is the measurement of this capacity. Measurements of muscle oxygen saturation (SmO2 ), blood lactate, and end tidal CO2 (EtCO2 ) have recently gained attention as prognostic tools for early assessment of the status of patients with progressive hemorrhage, but lack the ability to adequately differentiate individual tolerance to hypovolemia. We hypothesized that the CRM would better predict hemodynamic decompensation and provide greater specificity and sensitivity than metabolic measures. To test this hypothesis, we employed lower body negative pressure on healthy human subjects until symptoms of presyncope were evident. Receiver operating characteristic area under the curve (ROC AUC), sensitivity, and specificity were used to evaluate the ability of CRM, partial pressure of oxygen (pO2), partial pressure of carbon dioxide (pCO2), SmO2, lactate, EtCO2, potential of hydrogen (pH), base excess and hematocrit (Hct) to predict hemodynamic decompensation. The ROC AUC for CRM (0.94) had a superior ability to predict decompensation compared with pO2 (0.85), pCO2 (0.62), SmO2 (0.72), lactate (0.57), EtCO2 (0.74), pH (0.55), base excess (0.59), and Hct (0.67). Similarly, CRM also exhibited the greatest sensitivity and specificity. These findings support the notion that CRM provides superior detection of hemodynamic compensation compared with commonly used clinical metabolic measures.